How to revive beauty subscription boxes in Asia - MADAN, Shilpa (Institutional Knowledge at Singapore Management University, 2016)
After being acquired by consumer goods behemoth Unilever for a whopping $1 billion, Dollar Shave Club became the indisputable poster child of the subscription economy era. So will the next Dollar Shave Club come from Asia?